Skeletal stability in orthognathic surgery with the surgery first approach: a systematic review. Issue 7 (July 2019) - Soverina, D.; Gasparini, G.; Pelo, S.; Doneddu, P.; Todaro, M.; Boniello, R.; Azzuni, C.; Grippaudo, C.; Saponaro, G.; D'Amato, G.; Garagiola, U.; Moro, A.
Abstract: The surgery first approach (SFA) is a therapeutic strategy used in orthognathic surgery that is constantly evolving. With this approach, the pre-surgical orthodontic treatment can be eliminated, the maxilla and the mandible are surgically repositioned into the desired position, and the therapy is ended with a short orthodontic phase. Several studies have reported that the SFA is an acceptable approach, but postoperative stability is unclear. In this study, a systematic review on the SFA was performed. The PubMed, Google Scholar, Scopus, LexisNexis, Web of Science, and Cochrane Library databases were accessed. Studies from which data could be extracted on skeletal stability based on specific cephalometric points were included. The search yielded 2766 publications. Application of the selection criteria resulted in a final group of 14 articles. Five hundred and sixty patients with class III malocclusion underwent orthognathic surgery, 339 with the SFA. Study parameters such as evaluation time points and reference planes varied, making it impossible to perform a meta-analysis. The studies suggest that surgery with the SFA is as stable as surgery with the conventional approach. However, all articles described stability using a penultimate time point of 'after surgery' and not 'after debonding'; hence orthodontic movements and consequent mandibular movements could have influenced cephalometric measurements. Thus, to verify the real stability of the SFA, further research with longer follow-up periods is required, with evaluation at the same time points.